Current Tendencies of Judicial Review as Reflected in the New Hungarian Code of Administrative Court Procedure - Krisztina F. Rozsnyai (Central European Public Administration Review)
The continuing expansion of judicial review of administrative actions, as seen throughout Europe, led to the engulfment of the administrative judiciary towards the end of the last century. Review within a reasonable timeframe is hard to grant for this reason: the tensions between lawfulness and efficiency are amplified. The answers given to alleviate this tension raise questions that lie at the heart of the principle of separation of powers. This article aims to present some of respective tendencies, which lead to new equilibriums in the system of checks and balances between public administration and the judiciary. To concretise these tendencies, the article analyses some relevant solutions given by the very new code on administrative court procedures, the Hungarian Act No. I of 2017. The most important elements of the regulation of procedures for judicial review of administrative action are provided in a dogmatic and a comparative perspective showing the changes of rules and/or their interpretation through the judiciary. Thus, also important challenges regarding the present understanding of the doctrine of separation of powers are emphasised. The most important elements of the new Hungarian regulation are presented in a coherent system, which also gives insight on the codificational considerations. Moreover, the legislation and jurisprudence must deal with the highlighted aspects in any national and EU legal systems alike.